Growing Institutional Complexity and Field Transition: Towards Constellation Complexity in the German Energy Field - Stephan Bohn; Ali Aslan Gümüsay (Journal of Management Studies, 2023)
By applying a dynamic approach to field-level institutional complexity, we explore how growing institutional complexity affects fields over time. We examine field transition processes, which are shaped by the number of logics, the nature of their relationships and the shifts in dominance. Focusing on Germany's energy field, our analysis identifies a variety of conflicts that arose among up to seven institutional logics in the context of the German energy transition, i.e., the transition towards a low carbon energy market. The paper makes two theoretical contributions to the institutional complexity and field literature. First, we develop a process model explaining the field-level consequences of two different types of growing complexity, namely increasing and accelerating complexity. Second, we identify conflicting logic constellations as a distinct form of complexity that we term constellation complexity. We discuss our contributions in light of the literature on institutional logics and fields and show how applying a dynamic perspective to institutional complexity supports scholars in conceptualizing field transition processes.
Keywords: 650; field transition; institutional complexity; institutional logics; logic constellations; sustainability transition; topic modeling